Collective Leadership for Cultures of High Quality Health Care. Issue 3 (20th August 2014) - West, Michael; Lyubovnikova, Joanne; Eckert, Regina; Denis, Jean-Louis; Sparrow, Paul; Sparrow, Paul
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose The purpose of this paper is to examine the challenges that health care organizations face in nurturing and sustaining cultures that ensure the delivery of continually improving, high quality and compassionate care for patients and other service users. Design/methodology/approach Based on an extensive review of the literature, we examine the current and very challenging context of health care and highlight the core cultural elements needed to enable health care organizations to respond effectively to the challenges identified. Findings The role of leadership is found to be critical for nurturing high quality care cultures. In particular, we focus on the construct of collective leadership and examine how this type of leadership style ensures that all staff take responsibility for ensuring high quality care for patients. Practical implications Climates for quality and safety can be accomplished by the development of strategies that ensure leaders, leadership skills and leadership cultures are appropriate to meet the challenges health care organizations face in delivering continually improving, high quality, safe and compassionate patient care. Originality/value This paper provides a comprehensive integration of research findings on how to foster quality and safety climates in healthcare organizations, synthesizing insights from academic literature, practitioner reports and policy documents to propose clear, timely and much needed practical guidelines for healthcare organizations both nationally and internationally.